PENGARUH KOMPETENSI KARYAWAN, SISTEM PENGEMBANGAN SDM TERHADAP EFEKTIVITAS KERJA DIKANTOR PEGADAIAN MANGGELEWA, DOMPU NUSA TENGGARA BARAT - Nelis Elfiana; Epsilandri Septyarini (Fakultas Keguruan Dan Ilmu Pendidikan Universitas Pasundan, 2025)
This research aims to analyze and find out whether Employee Competency and HR Development System Affect Work Effectiveness at the Manggelewa Pawnshop Office, Dompu, West Nusa Tenggara. This research involved employees who worked at the Manggelewa pawnshop office, Dompu NTB. The sample of respondents used in this research was 59 employees. In this research, total sampling or saturated sampling techniques were applied. This method applies data analysis to determine validity, reliability, descriptive statistical analysis, classical assumptions, including normality, multicollinearity, and heteroscedasticity analysis, multiple regression analysis, partial test (t), simultaneous test (F), and coefficient of determination test (R2) . The results of this research are based on the partial test (t) of Employee Competence on Work Effectiveness, obtained by a t-count of 0.016 < 0.05, so it can be concluded that Ho is rejected. H1 is accepted, thus it can be concluded that the Employee Competency variable applied in this research has a positive effect on Work Effectiveness. The HR Development System on Work Effectiveness obtained a significance level of 0.000 < 0.05 so it can be concluded that Ho is rejected and H2 is accepted. The Employee Competency (X1) and HR Development System (X2) variables influence Work Effectiveness (Y) simultaneously, with a significant value (0.000 < 0.05). The calculation results of the Fcount > Ftable test are, 79.811 > 3.162).